Chest wall perforator flap reconstruction in breast conserving surgery: quality of life and limited complications in outpatient treatment - L. J. van Zeelst; R. Straten; R. R. J. P. van Eekeren; D. J. P. van Uden; J. H. W. de Wilt; L. J. A. Strobbe (World Journal of Surgical Oncology)
Abstract Background Breast conserving surgery (BCS) with partial breast reconstruction (PBR) results in less morbidity, better cosmetic outcomes, and improved patient satisfaction compared to mastectomy. Perforator flap reconstruction can attenuate defects prone to breast deformity after BCS. Usually, postoperative drains and inpatient admission are part of this treatment. The main objective of this study is to report on postoperative complications and patient satisfaction after drainless perforator flap reconstruction by a dedicated breast surgeon. Methods In a retrospective case series, 42 patients were included. All patients underwent BCS with drainless perforator flap reconstruction, planned and performed by a single breast surgeon. Outcomes were complication incidence and patient satisfaction reported in the Breast-Q Breast Conserving Therapy (BCT) module. Results In the study cohort, the median age was 59.5 (49.8–71.3) years. Tumour types were ductal carcinoma in situ (DCIS, four patients, 9.5%), invasive no special type (NST, 22 patients, 52.4%), invasive lobular (12 patients, 28.6%), and other invasive cancers (4 patients, 9.5%). Complication incidence was seven of 42 patients (16.7%), including hematoma, seroma, wound dehiscence, fat necrosis, and lymphedema, all Clavien Dindo grade 0–1, without readmission or reoperation. Reported Breast-Q scores (median of 17 months after surgery) were 87/100 for psychosocial well-being, 82/100 for breast satisfaction, and 71/100 for physical well-being. Outpatient treatment was successful in 38 patients (90.5%), and 13 patients (31.0%) had an unplanned visit to the outpatient clinic. Conclusion Drainless perforator flap reconstruction performed by the breast surgeon results in high patient satisfaction and limited complications, both in number and severity. The use of drains and hospital stays after perforator flap reconstruction must be discouraged.